2021
DOI: 10.1055/s-0040-1722310
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Online Resources by Patients in an Ophthalmic Emergency Department

Abstract: Objective To describe the utilization of online resources by patients prior to presentation to an ophthalmic emergency department (ED) and to assess the accuracy of online resources for ophthalmic diagnoses. Methods This is a prospective survey of patients presenting to an ophthalmic ED for initial evaluation of ocular symptoms. Prior to evaluation, patients completed surveys assessing ocular symptoms, Internet usage, and presumed self-diagnoses. Demographics and characteristics of Internet usage wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…19 The accuracy of medical information in ophthalmology is inconsistent across different online platforms, including YouTube and Wikipedia. [20][21][22][23][24] Similarly, reviews of online information in plastic surgery found considerable amounts of misleading or inaccurate claims. [25][26][27][28] Clinically inaccurate content can be particularly dangerous for patients seeking information about postprocedural complications, expectations, or acute recovery.…”
Section: Discussionmentioning
confidence: 99%
“…19 The accuracy of medical information in ophthalmology is inconsistent across different online platforms, including YouTube and Wikipedia. [20][21][22][23][24] Similarly, reviews of online information in plastic surgery found considerable amounts of misleading or inaccurate claims. [25][26][27][28] Clinically inaccurate content can be particularly dangerous for patients seeking information about postprocedural complications, expectations, or acute recovery.…”
Section: Discussionmentioning
confidence: 99%